THE WORD SOOTVETSTVENNO IN ORAL DISCOURSE: SEMANTIC FEATURES, DISCOURSE FUNCTIONS, AND PROSODIC CHARACTERISTICS - Aleksandra A. Aisanova; Diana D. Marchenyak (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Phenomena characteristic of natural oral speech are actively studied in modern linguistic. Within this form of speech, a number of non-significant lexical units develop new meanings/functions. The description of such transformations allows to see, on the one hand, the semantic and discursive potential of the analyzed language elements, and on the other, the features of functioning in this form of speech that are common to different words.